Matrine induces apoptosis and autophagy of glioma cell line U251 by regulation of circRNA-104075/BCL-9. (1st August 2019) - Chi, Guonan; Xu, Donghui; Zhang, Boyin; Yang, Fuwei
Abstract: Background: Matrine, a traditional Chinese medicine, has been reported to exert anti-tumor effects in several types of cancers. Here, we explored the anti-tumor effects of matrine on the glioma cells. Methods: Glioma cell line U251 cells were treated with matrine to assess viability and proliferation using CCK8 and EdU assays. PI/FITC staining was performed for apoptosis assay. Transfections were performed for circRNA-104075 or Bcl-9 overexpression. Western blot analysis was performed to evaluate changes of protein levels and changes of gene level were detected by qRT-PCR in U251 cells. Results: Matrine suppressed cell viability while induced apoptosis and autophagy in U251 cells. Matrine also decreased circRNA-104075 expression significantly. Overexpression of circRNA-104075 was found to counteract the inhibitory effects of matrine on cell proliferation and promoting effects on apoptosis and autophagy in U251 cells. Moreover, the suppressed Wnt/β-catenin and PI3K/AKT signaling pathways by matrine were activated by circRNA-104075 overexpression. Furthermore, Bcl-9 expression was also down-regulated by matrine treatment. Bcl-9 overexpression elevated the decreased cell proliferation while suppressed the increased apoptosis and autophagy induced by matrine in U251 cells. Conclusion: Taken together, the present findings suggested that matrine induced apoptosis and autophagy through down-regulating circ-104075 and Bcl-9 expression via inhibition of PI3K/AKT and Wnt-β-catenin pathways in glioma cells. The present study provides a foundation for further preclinical and clinical evaluations of matrine as a glioma therapy. Highlights: The anti-tumor effects of matrine on glioma have been explored. CircRNA-104075 plays an important role in the anti-tumor effects of matrine in glioma. Inhibition of circRNA-104075 or Bcl-9 can help to suppress glioma progression.